The clinical efficacy of piroxicam fast-dissolving dosage form for postoperative pain control after simple lumbar spine surgery: A double-blinded randomized study - Chathchai Pookarnjanamorakot (2018)
Study Design. A prospective, randomized, double-blinded clinical trial was conducted. Objective. To study the efficacy of piroxicam fast-dissolving dosage form in reducing postoperative pain after simple lumbar spine surgery. Summary of Background Data. Many reports mention the use of nonsteroidal antiinflammatory drug for relieving postoperative pain, but study still is lacking on their use in spine surgery. Methods. For this study, 50 patients who underwent discectomy or one-level laminectomy were randomly sampled into two groups: 21 patients in the placebo control group and 29 patients in the study group. In addition to a normal postoperative analgesic regimen, each patient received placebo or piroxicam fast-dissolving dosage form (2 tablets administered sublingually 1 to 3 hours before surgery). This regimen was repeated with 2 tablets after 24 hours, then 1 tablet after 48 hours. Postoperative pain was evaluated every 6 hours by a visual analog scale for 3 days. The amount of morphine usage was measured on postoperative days 1, 2, and 3. Postoperative variables such as blood loss, length of wound, and time of operation also were recorded. Results. There was no difference between the groups with respect to age, weight, height, gender, and type of operation. The postoperative pain of the study group, as measured by visual analog scale, showed significant improvement (P < 0.05) during the postoperative period 12 to 42 hours after surgery. The study group used less morphine, but their usage showed no significant difference on postoperative days 1, 2, and 3. When the visual analog scale between the types of operation was compared, the scale for the discectomy group was better than that for the laminectomy group. The results of the postoperative variables showed no difference between the groups in terms of postoperative blood loss, length of wound, and time of operation. Conclusions. Sublingual administration of piroxicam fast-dissolving dosage form after simple spine surgery is effective and efficient in relief of postoperative pain. Because of its low side effects and high toleration, piroxicam fast-dissolving dosage form may be considered as an alternative for postoperative pain control during the early postoperative period.